PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MATERI HIDROKARBON DALAM MENINGKATKAN HASIL BELAJAR KOGNITIF PESERTA DIDIK - Yuliana Mariana; Siti Maesyaroh (Universitas Papua, Manokwari, Indonesia, 2021)
AbstractThe education had important role in efforts to progress in the future. The purpose of this study was to improve student learning outcomes through the application of the Problem Based Learning learning model on the colligative nature of the solution in class XII IPA SMA YPK Immanuel Manokwari and to see the large increase in student learning outcomes on the subject matter of the colligative nature of the solution. This study used a classroom action research model (PTK) with Kurt Lewis's CAR model which consisted of two cycles with each cycle having four stages, namely planning, action, observation and reflection. The increase in student learning result can be seen from the pre-test and post-test results that have been given to students. The data obtained were then analyzed using descriptive analysis techniques with the help of Microsoft Excel 2010 to describe the improvement in each cycle. After being analyzed, it is seen that the application of the Problem Based Learning learning model can improve the learning outcomes of students in class XII IPA SMA YPK Immanuel Manokwari on the colligative nature of the solution. This can be seen from the increase in learning outcomes of students who have reached KKM ≥ 70 in cycle I by 40%, increasing by to 80% at the end of cycle 2 with high classical completeness. In addition, there is an increase in the average learning outcomes of cycle 1 by 56.33 to cycle 2 by 72.68. Keywords: Problem Based Learning, learning outcomes, colligative solution, Classroom Action Research